Early Endothelialization of Ab Interno Stromal Tectonic Patch in the Management of Corneal Perforation Secondary to Bacterial Keratitis. Issue 6 (22nd June 2022) - Roberts, Harry W.; Davidson, Max; Thaung, Caroline; Myerscough, James
Abstract : Purpose: The purpose of this study was to describe a novel surgical technique using an ab interno stromal patch to treat corneal perforation and to present the histological findings of the patch after its removal during definitive mushroom keratoplasty. Methods: The endothelium had already been removed with the submerged cornea using backgrounds away (SCUBA) technique. Results: The patient was managed successfully with a sutureless ab interno stromal tectonic patch. Two months later, definitive mushroom keratoplasty was performed and the patch was sent for histological examination. Immunohistochemistry revealed a reactive endothelium covering the posterior surface of the graft. Nine months later, her best-corrected visual acuity was 6/9. Conclusions: This is the first case to our knowledge demonstrating that stromal tectonic grafts without the endothelium can successfully attach to the host tissue and seal a perforation. The stroma may undergo reendothelialization and begin to restore vision, even before penetrating keratoplasty.